Ag22 Nanoclusters with Thermally Activated Delayed Fluorescence Protected by Ag/Cyanurate/Phosphine Metallamacrocyclic Monolayers through In‐Situ Ligand Transesterification. (7th October 2022) - Yuan, Zhi‐Rui; Wang, Zhi; Han, Bao‐Liang; Zhang, Cheng‐Kai; Zhang, Shan‐Shan; Zhu, Zhen‐Yu; Yu, Jiu‐Hong; Li, Tian‐Duo; Li, Ying‐Zhou; Tung, Chen‐Ho; Sun, Di
Abstract: The composition of protection monolayer exerts great influence on the molecular and electronic structures of atomically precise monolayer protected metal nanoclusters. Four isostructural Ag/cyanurate/phosphine metallamacrocyclic monolayer protected Ag22 nanoclusters are synthesized by kinetically controlled in‐situ ligand formation‐driven strategy. These eight‐electron superatomic silver nanoclusters feature an unprecedented interfacial bonding structure with diverse E‐Ag (E=O/N/P/Ag) interactions between the Ag13 core and metallamacrocyclic monolayer, and displays thermally activated delayed fluorescence (TADF), benefiting from their distinct donor‐acceptor type electronic structures. This work not only unmasks a new core‐shell interface involving cyanurate ligand but also underlines the significance of high‐electron‐affinity N‐heterocyclic ligand in synthesizing TADF metal nanoclusters. This is the first mixed valence Ag 0/I nanocluster with TADF characteristic. Abstract : Four isostructural Ag22 nanoclusters protected by a metallamacrocyclic monolayer were synthesized in high yields by in‐situ ligand formation strategy. The high‐electron‐affinity triazine‐based cyanurate ligands endow the clusters with unique core‐shell interfacial bonding structure and donor‐acceptor type electronic structure, resulting in the first mixed valence Ag 0/I nanocluster with thermally activated delayed fluorescence (TADF) characteristic.